2021
DOI: 10.1186/s12885-020-07692-6
|View full text |Cite
|
Sign up to set email alerts
|

A gene-based risk score model for predicting recurrence-free survival in patients with hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) remains the most frequent liver cancer, accounting for approximately 90% of primary liver cancers worldwide. The recurrence-free survival (RFS) of HCC patients is a critical factor in devising a personal treatment plan. Thus, it is necessary to accurately forecast the prognosis of HCC patients in clinical practice. Methods Using The Cancer Genome Atlas (TCGA) dataset, we identified genes associated with RFS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…We then validated the reliability and prediction performance of gene signature in two independent HCC cohorts (TCGA HCC cohort and GSE76427 dataset). Compared with existing signatures, our prognostic model exhibited better performance to predict the RFS of HCC patients [28,29].…”
Section: Discussionmentioning
confidence: 95%
“…We then validated the reliability and prediction performance of gene signature in two independent HCC cohorts (TCGA HCC cohort and GSE76427 dataset). Compared with existing signatures, our prognostic model exhibited better performance to predict the RFS of HCC patients [28,29].…”
Section: Discussionmentioning
confidence: 95%
“…A total of 21 genes were intersection of those identified by differentially expression analysis and univariate Cox regression analysis. After that, a robust likelihood-based survival modeling approach was used to narrow the number of genes and select the best genes for the prognostic model using “survminer” and “survival” R package ( Wang et al, 2021c ). Finally, a total of 11 genes were screened to construct the risk model by using the multivariate Cox regression analysis with a parameter of “direction = both.” To evaluate the survival risk of patients with CRC, a prognostic risk model was constructed using risk coefficients and gene expression as described in previous studies ( Zhang et al, 2020 ; Liu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Risk score for the signature was evaluated as following algorithm: Riskscore = Coef gene1 *expression gene1 + Coef gene2 *expression gene2 + Coef gene3 *expression gene3 + ...... + Coef genen *expression genen (where “Coef” and “expression” are respectively the coefficient and RNA relative expression value, “gene” represents each selected gene range from 1 to n) ( Wang et al, 2020b ). Briefly, firstly, a robust likelihood-based survival modeling approach was used to narrow the number of genes from 21 key LMGs and the best genes were selected for the prognostic model using “survminer” and “survival” R package ( Wang et al, 2021c ). Secondly, multiple Cox regression analysis was performed to establish prognostic risk model using “survival” R package with a parameter of “direction = “both” ( Wang et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…This multivariate analysis suggested that the machine learning risk score (HR = 1.5, p = 0.015), AFP values (HR = 1.74, p = 0.012) and TNM staging (HR = 2.01, p = 0.01 for stage III + IV) were all independent recurrence indicators of HCC. Similar studies have been carried out where multiple gene signatures were created and validated with AI assistance and machine learning algorithms in the hopes of prediction of HCC recurrence [63][64][65].…”
Section: The Role Of Ai In Facilitating Biomarkers To Predict the Rec...mentioning
confidence: 98%